Determining Millimeter‐Scale Maps of Cation Exchange Capacity at Macropore Surfaces in Bt Horizons - Leue, M. (2020)
To determine effective CEC (CECeff), a reduction of soil mass down to 0.5 g for use in the standard barium chloride batch method was tested to account for the limited amount of soil material that can be separated from thin macropore coatings. Linear and partial least squares regression analyses were applied to predict the CECeff distribution at intact macropore surfaces for samples from Luvisol Bt horizons from loess (L) and glacial till (T) using DRIFT spectral data. The highest CECeff values were found for coatings and pinhole fillings rich of clay–organic material (L: 38 cmol kg−1; T: 29 cmol kg−1) compared with low CECeff values of uncoated cracks and earthworm burrows that were similar to those of bulk soil (L: 21 cmol kg−1; T: 14 cmol kg−1). The location of millimeter‐ to centimeter‐sized regions with increased CECeff levels at intact macropore surfaces corresponded with the location of clay–organic coatings. The proposed method allows determining the CEC at macropore surfaces to quantify their effect on nutrient transport by preferential flow as well as on plant nutrient supply in macropores that may serve as preferential growth paths for plant roots.